Exploring Pathways for Mobile Interaction Technologies to Foster Innovation in Entrepreneurial Education Models - Ye, Jibo (International Journal of Interactive Mobile Technologies (iJIM), 2024)
With the rapid advancement of information technology, mobile interaction technologies have emerged as a pivotal force driving educational innovation, especially in the realm of entrepreneurial education. These technologies have not only transformed the methods of acquiring and sharing knowledge but have also facilitated interaction and collaboration among learners. This investigation aims to explore how mobile interaction technologies can foster innovation in entrepreneurial education models. The focus is specifically placed on the construction of a mobile interaction-based collaborative learning team environment model oriented towards knowledge building as well as on identifying collaborative strategies that can effectively enhance entrepreneurial learning teams based on mobile localized influence networks. It has been discovered that optimizing mobile learning environments and collaborative strategies improves the quality of interaction and learning outcomes among teams, providing new pathways for entrepreneurial education. Existing research, however, lacks a comprehensive discussion on the deep integration of mobile interaction technologies with entrepreneurial education, especially in terms of systematic studies on team collaboration and the process of knowledge construction. Through theoretical exploration and empirical analysis, this manuscript aims to bridge the research gap, providing theoretical and practical support for innovation in entrepreneurial education models. This endeavor holds significant research value and practical implications.